Optimisation of the parameters of the matching layer of a piezoelectric transducer by the finite element method - Dedovich, Nikolai N.; Kuchynski, Petr V.; Romanov, Anatoly F. (Journal of the Belarusian State University. Physics, 2026)
A methodology for finding the optimal parameters of the matching layer of a piezoelectric transducer designed to convert and receive ultrasonic vibrations in a gas is presented. As a way to optimise the parameters of the matching layer, modelling of a piezoelectric transducer by the finite element method using the COMSOL Multiphysics software package is used. Models of a piezoelectric transducer are presented and optimisation of the parameters of the matching layer is implemented in order to increase the efficiency of electrical signal conversion into ultrasonic vibrations and vice versa. The obtained models allow to estimate the frequency characteristics of a piezoelectric transducer and to analyse the efficiency of mutual conversion of electrical and ultrasonic energy, as well as the process of propagation of ultrasonic waves. It is shown that the finite element modelling method allows to establish requirements for the material and geometry of the matching layer of a piezoelectric transducer, and a slight complication of the model makes it possible to predict the operation of piezoelectric transducers in the mode of radiation and reception of ultrasonic signals in a gas environment during the design and manufacture of prototypes.